The BUDDY (Bedside Ultrasound to Detect Dehydration in Youth) study - Jauregui, Joshua (Crit Ultrasound J, 2014)
BACKGROUND: Prior research suggests that the ratio of the ultrasound-measured diameter of the inferior vena cava to the aorta correlates with the level of dehydration in children. This study was designed to externally validate this and to access the accuracy of the ultrasound measured inspiratory IVC collapse and physician gestalt to predict significant dehydration in children in the emergency department. METHODS: We prospectively enrolled a non-consecutive cohort of children ≤18 years old. Patient weight, ultrasound measurements of the IVC and Ao, and physician gestalt were recorded. The percent weight change from presentation to discharge was used to calculate the degree of dehydration. A weight change of ≥5% was considered clinically significant dehydration. Receiver operating characteristic (ROC) curves were constructed for each of the ultrasound measurements and physician gestalt. Sensitivity (SN) and specificity (SP) were calculated based on previously established cutoff points of the IVC/Ao ratio (0.8), the IVC collapsibility index of 50%, and a new cut off point of IVC collapsibility index of 80% or greater. Intra-class correlation coefficients were calculated to assess the degree of inter-rater reliability between ultrasound observers. RESULTS: Of 113 patients, 10.6% had significant dehydration. The IVC/Ao ratio had an area under the ROC curve (AUC) of 0.72 (95% CI 0.53 to 0.91) and, with a cutoff of 0.8, produced a SN of 67% and a SP of 71% for the diagnosis of significant dehydration. The IVC collapsibility index of 50% had an AUC of 0.58 (95% CI 0.44 to 0.72) and, with a cutoff of 80% collapsibility, produced a SN of 83% and a SP of 42%. The intra-class correlation coefficient was 0.83 for the IVC/Ao ratio and 0.70 for the IVC collapsibility. Physician gestalt had an AUC of 0.61 (95% CI 0.44 to 0.78) and, with a cutoff point of 5, produced a SN of 42% and a SP of 65%. CONCLUSIONS: The ultrasound-measured IVC/Ao ratio is a modest predictor of significant dehydration in children. The inspiratory IVC collapse and physician gestalt were poor predictors of the actual level of dehydration in this study.